ANALISIS RASIO SOLVABILITAS DAN PROFITABILITAS TERHADAP PERUBAHAN LABA PADA PT.LATINUSA, Tbk TAHUN 2014 – 2018 - Noviyanti Wulandari Sitepu (Jurnal Akuntansi Indonesia, 2018)
The formulation of the problem in this study are: 1) How does the influence of Debt To Asset Ratio on changes in earnings of PT. Latinusa, Tbk in 2014-2018? 2) How does the influence of Debt To Equity Ratio on changes in earnings of PT. Latinusa, Tbk in 2014-2018? 3) How does the influence of Net Profit Margin on changes in profits of PT. Latinusa, Tbk in 2014-2018? 4) What is the effect of Return On Equity (ROE) on changes in earnings of PT. Latinusa, Tbk in 2014-2018? 5) How does the effect of Return On Total Assets (ROA) on changes in earnings of PT. Latinusa, Tbk in 2014-2018? The method used in this research is descriptive analysis method. Data collection techniques used are documentation and literature study, while data analysis techniques used in this study to assess the effect of the solvency ratio on earnings changes are Debt To Asset Ratio, Debt To Equity Ratio. Assessing the effect of the solvency ratio on earnings changes namely Net Profit Margin, Return On Equity and Return On Total Assets. Based on the results of the study "Analysis of Solvency Ratios and Profitability Ratios to Changes in Profit of PT.Latinusa, Tbk in 2014-2018 listed on the Indonesian Stock Exchange", it can be concluded that the solvency ratio of PT. Latinusa, Tbk during 2014-2018 on Debt To Asset Ratio and Debt To Equity Ratio has an insecure level of ratio so that the solvency of PT. Latinusa, Tbk is not solvable or unfavorable because the company is still financed by a large enough debt. While the profitability ratio of PT. Latinusa, Tbk during 2014-2018 on Net Profit Margin, Return On Asset and Return On Equity has an unfavorable ratio level so that the profitability of PT. Latinusa, Tbk in a condition of inability to make a profit. PT. Latinusa, Tbk from 2014-2018 experienced fluctuations that showed the ups and downs of the company's revenue. This shows that PT. Latinusa, Tbk should increase its sales so that its income also increases so as to make the level of profitability increase, and minimize short-term and long-term debt to make the level of solvency of PT. Latinusa, Tbk increased. Keywords: Solvency, Profitability, and Changes in Profit